Extraction of Sesquiterpene Lactones from Inula helenium Roots by High-Pressure Homogenization and Effects on Antimicrobial, Antioxidant, and Antiglycation Activities - Ozcan, Fahriye Seyma; Ozcan, Nihat; Meral, Hilal Dikmen; Cetin, Ozlem; Celik, Mustafa; Trendafilova, Antoaneta (SPRINGER, 2024)
The sesquiterpene lactones (SL) of Inula helenium (I. helenium) roots were extracted using high-pressure homogenization (HPH) and compared against those derived from maceration. The effect of process conditions on the extraction efficiency of bioactive compounds (alantolactone, isoalantolactone, total phenols, and flavonoids); the 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical-scavenging activity, ferric-reducing antioxidant power (FRAP), and antimicrobial activity of the extract; and the inhibition of advanced glycated end product (AGE) formation were assessed. The HPH of 90 MPa for 4 passes demonstrated the highest alantolactone (38.1 +/- 0.7 mg/g) and isoalantolactone yields (34.4 +/- 0.2 mg/g), respectively, which were significantly higher than the rates obtained using maceration (20.0 +/- 0.2 mg/g and 18.9 +/- 0.7 mg/g). Under optimal extraction conditions of 90 MPa for 4 passes, inhibition of AGE formation in the extract reached a rate of 97.16 +/- 1.86%, with the highest DPPH and FRAP of 231.63 +/- 2.96 mu g/mL and 949.43 +/- 1.86 mu mol TE/100 mL, respectively. HPH exhibited lethal activity against all tested bacteria and fungi strains (Escherichia coli, Staphylococcus aureus, Listeria monocytogenes, Aspergillus niger, Fusarium oxysporum, and Penicillum expansum) at a concentration of 15 mu L. SEM results proved that HPH severely damaged the cell structures of roots, increased solvent permeability, and improved the extraction rate of bioactive compounds. Additionally, this study also demonstrated that HPH yields high recovery with a specific energy consumption of 0.22 kWh/kg, which is close to the recommended minimum energy demand for an extraction procedure within industrial production processes. Therefore, these findings showed that HPH can be used as an efficient extraction technique for the production of SL in related industries.
Keywords: High-pressure homogenization; Sesquiterpene lactones; Antiglycation activity; Antioxidant capacity; Antimicrobial activity; LC-MS/MS; ULTRASOUND-ASSISTED EXTRACTION; BIOACTIVE COMPOUNDS; ISOALANTOLACTONE; ALANTOLACTONE; Food Science & Technology